Quantitative measures for gastrointestinal MRI - Williams, Hannah (2020)
The use of Magnetic Resonance Imaging (MRI) as both a clinical and research tool has increased substantially over the last 40 years. However, one area of use that has seen a smaller benefit from this increase is the structure and function of the gastrointestinal system. Faster acquisition methods and improved computer analysis techniques now mean that measures that are routinely made outside of the abdomen can start to be utilised in the gastrointestinal system.